(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The study investigatesthe relationshipmarketing(RM) strategy of Hotel industry and examines whether after the implementation-customer relationships were strengthened through perceived improvements in the Hotel industry and consequently loyalty towards the Hotel.